Perancangan User Experience pada Aplikasi Prabumart dengan Metodologi Design Thinking - Muhammad Redo; Andi Reza Perdanakusuma; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Prabumulih City Women's Farmer's Group It is a program of the Mayor of Prabumulih. Access and minimal information in the area per sub-district of Prabumulih City makes the sales of KWT less than optimal, therefore the Prabumulih City Government plans to develop the Prabumart application. The user experience design must be followed because the application design must provide a good experience when used by the community. Design thinking is a method used to create user experiences on Prabumart applications by identifying problems and explaining designs that can solve existing problems. The solution is then tested using a User Experience Question (UEQ), which helps determine whether the solution was developed or completed by the application's user resources. In addition, the test uses UEQ, for example, users of the Prabumulih City community and the Prabumart application, the mean value of each UEQ scale is in the positive category with all UEQ scales in the excellent category very good, then for the Prabumart Admin application with users of the Women Farmers Group. has a mean value for each UEQ scale which is also in the positive category with all UEQ scales being in the above average category for the Attractiveness scale in the good category. In the feedback capture matrix test, there are recommendations for improvement from 3 users.